Prospect, Legal, and Health Risks in Adopting The Metaverse in Medical Practice: a Case Study of Nigeria - Aidonojie, Paul Atagamen; Aidonojie, Esther Chetachukwu; Eregbuonye, Obieshi; Abacha, Saminu Wakili; Okpoko, Mercy (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2024)
The Metaverse provides a prospective opportunity for medical practitioners to improve patient engagement, training of medical personnel, and simulation-based learning. It allows for immersive telemedicine medical practice, enabling medical practitioners to render medical services to patients in remote areas through realistic virtual consultation and training of medical personnel and students through a lifelike simulation. However, despite the potential of the Metaverse concept in medical practice, certain legal and medical issues could mitigate its usefulness. In this regard, this study adopts a hybrid method of research in ascertaining the prospect, legal, and health risks of utilizing the metaverse in medical practice. 256 questionnaires were distributed, and the result obtained was analysed using descriptive and analytical methods. The study found that there are several potentials for utilizing the metaverse in medical practice. However, there are legal and medical risks in utlising the metaverse in medical practice and they include; patient data privacy, regulation, licensing, patient consenting to virtual medical treatment, and accountability for medical errors in the metaverse. Furthermore, the study also found that spending longer hours in the metaverse could result in sedentary behavior, associated with medical issues like obesity, musculoskeletal disorders, and cardiovascular problems. It was therefore concluded and recommended that the metaverse holds significant promise for the future of medical practice in Nigeria, offering innovative solutions that can transform healthcare delivery and education. However, to avoid legal and medical issues that may occur, there is a need for regulatory compliance with healthcare regulations.